Natural Conditioning of the Spiritual Life: A Contribution to Methodological Reflection - Matuszewski, Krzysztof Marek (Verbum Vitae, 2020)
The spiritual life constitutes an integral experience of any person being led by the Holy Spirit toward full communion with God. It is never something abstract, divorced from Sitz im Leben, in either the psychological aspect or the socio-cultural dimension, thus it always bears certain signs of one’s temperament, environment, and history. The present paper proposes a methodology of research into the natural basis of the spiritual life (psychological and socio-cultural), which influences the way God’s grace is received and experienced. The natural structures of the spiritual life constitute the ground, which is submitted to God’s salvific action and bears fruit in various forms. The description of the spiritual life demands the use of the appropriate methodology, which can be based on the combination of the doctrinal-sapiential (deductive) approach and the existential-anthropological (inductive) approach. An important auxiliary role in the description of the spiritual phenomenon can be played by psychological methods, for instance those that derive from the psycho-biographical approach, which allows us to capture what is unique in human functioning.